Teologi Publik: dari Fanatisme Agama menuju Memelihara Kehidupan Bersama - Sitorus, Angga; Sihaloho, Lamhot Augustinus; Chandra, Michael (VISA: Journal of Vision and Ideas, 2026)
This study aims to explore a way of thinking that shifts from religious fanaticism to preserving communal life. This study employs a reflective and interpretive approach. This approach is used to interpret and reflect on Jurgen Habermas's thinking on the position of religious argumentation in the public sphere, critical hermeneutics, and Alain Badiou's approach to the procedure of truth. The data collection technique used was literature observation. The results of this study conclude that theology in the public sphere means striving to implement universal values, such as justice and equality for every citizen. This effort is inseparable from the creation of an equal space free from the dominance of particular beliefs and cultural interests. Furthermore, the growing phenomenon of religious fanaticism in the public sphere demands that we employ critical hermeneutics as a method that can encourage self-reflection.